The Mentors in Violence Prevention programme: impact on students' knowledge and attitudes related to violence, prejudice, and abuse, and willingness to intervene as a bystander in secondary schools in England - Nadia Butler; Zara Quigg; Charley Wilson; Ellie McCoy; Rebecca Bates (BMC, 2024)
Abstract Background Violence is a leading cause of death and disability for young people and has serious impacts on prospects across the lifecourse. The education sector is a crucial setting for preventing youth violence through incorporating programmes that address attitudes and behaviours. The Mentors in Violence Prevention (MVP) programme aims to change harmful attitudes and norms, and increase non-violent bystander intervention, through a peer mentoring approach. To date there is limited evidence on the effectiveness of the intervention in UK school settings. The aim of the current study was to evaluate the impact of the programme on students' attitudes and knowledge related to violence prevention. Methods The study employed a mixed methods design. Pre and post surveys measured changes in students' (aged 11-18) attitudes and knowledge related to violence prevention and bystander behaviour, gender stereotyping, acceptability of violence, and perceptions of others' willingness to intervene. Interviews/focus groups with programme delivers and students, and anonymised programme data were used to explore and supplement survey findings. Results Overall, perceptions of the programme content and delivery were positive. Several beneficial impacts of the programme were found for mentors (students delivering the programme), including significant positive changes on measures of knowledge and attitudes towards violence prevention and the bystander approach, acceptability of violence perpetration, and perceptions of other students' willingness to intervene (effect sizes were small-medium). However, the study found no significant change on any of the outcomes amongst mentees (younger students receiving the programme from mentors). Despite this, qualitative evidence suggested mentees enjoyed the content of the programme and the peer-led delivery, and this built relationships with older students. Qualitative evidence also identified additional benefits of the programme for mentors, including leadership and communication skills, and increased confidence and supportive relationships. Conclusions Evidence from this study suggests MVP is effective as a targeted programme for mentors, but no significant evidence was found to demonstrate its effectiveness as a universal bystander and violence prevention programme for mentees. Whilst further research with more robust study design is needed, developing mentors as leaders in violence prevention is a valuable impact of the programme in its own right.